Histone H3K4me3 modification is a transgenerational epigenetic signal for lipid metabolism in Caenorhabditis elegans - Wan, Qin-Li; Meng, Xiao; Wang, Chongyang; Dai, Wenyu; Luo, Zhenhuan; Yin, Zhinan; Ju, Zhenyu; Fu, Xiaodie; Yang, Jing; Ye, Qunshan; Zhang, Zhan-Hui; Zhou, Qinghua (Nature communications, 2022)
As a major risk factor to human health, obesity presents a massive burden to people and society. Interestingly, the obese status of parents can cause progeny’s lipid accumulation through epigenetic inheritance in multiple species. To date, many questions remain as to how lipid accumulation leads to signals that are transmitted across generations. In this study, we establish a nematode model of C. elegans raised on a high-fat diet (HFD) that leads to measurable lipid accumulation, which can transmit the lipid accumulation signal to their multigenerational progeny. Using this model, we find that transcription factors DAF-16/FOXO and SBP-1/SREBP, nuclear receptors NHR-49 and NHR-80, and delta-9 desaturases ( fat-5 , fat-6 , and fat-7 ) are required for transgenerational lipid accumulation. Additionally, histone H3K4 trimethylation (H3K4me3) marks lipid metabolism genes and increases their transcription response to multigenerational obesogenic effects. In summary, this study establishes an interaction between a network of lipid metabolic genes and chromatin modifications, which work together to achieve transgenerational epigenetic inheritance of obesogenic effects. Transgenerational inheritance (TEI) mechanisms are to some extent conserved across species, but how TEI mediates lipid accumulation is unknown. Here the authors reveal that a network of lipid metabolic genes and chromatin modifications mediated by transcription factors and H3K4 trimethylation work together to achieve multigenerational obesogenic effects in C. elegans fed with a high-fat diet.